Comprehensive diagnostic ability of endocytoscopy compared with biopsy for colorectal neoplasms: a prospective randomized noninferiority trial - Mori, Y.; Kudo, S.; Ikehara, N.; Wakamura, K.; Wada, Y.; Kutsukawa, M.; Misawa, M.; Kudo, T.; Kobayashi, Y.; Miyachi, H.; Yamamura, F.; Ohtsuka, K.; Inoue, H.; Hamatani, S. (Endoscopy, 2013)
Background and study aims: Endocytoscopy enables observation at 450-fold magnification during gastrointestinal endoscopy, allowing on-site “optical biopsy.” We compared the accuracies of endocytoscopy and standard biopsy for the diagnosis of colorectal neoplasms. Patients and methods: We performed a randomized, controlled, open-label trial of patients with colorectal lesions ( ≥ 5 mm) detected during colonoscopy in a tertiary referral center. We randomly assigned the 203 detected lesions of 170 eligible patients to either the endocytoscopy or standard biopsy group. An on-site endoscopist assessed the histopathology of the endocytoscopy group lesions according to the endocytoscopic findings, whereas a pathologist later assessed standard biopsy group lesions by microscopic examination of the biopsy specimens. We calculated the diagnostic accuracies in both groups with reference to the final histopathology of the resected specimens. The primary endpoint was to determine whether the diagnostic accuracy of endocytoscopy for neoplastic lesions was noninferior to that of standard biopsy (with a predefined noninferiority margin of 10 %). Analyses were by intention-to-treat and per-protocol. The study is registered, number UMIN000003923. Results: Overall, 102 lesions in the endocytoscopy group and 101 in the standard biopsy group were available for primary outcome analysis. There were no complications. The diagnostic accuracy of endocytoscopy for the discrimination of neoplastic lesions was 94.1 % (95 % confidence interval 87.6 % to 97.8 %), whereas that of standard biopsy was 96.0 % (90.2 % to 98.9 %), which is within the noninferiority margin (absolute difference − 1.9 %, − 8.6 % to + 5.0 %). Conclusions: Endocytoscopy is noninferior to standard biopsy for the discrimination of neoplastic lesions. With its advantage of providing an on-site diagnosis, endocytoscopy could provide a novel alternative to standard biopsy in routine colonoscopy.